TASAWUF SOSIAL DAN SOLUSI KRISIS MORAL - Achlami, HS, H.MA. (Universitas Islam Negeri Raden Intan Lampung, 2015)
During the 20th century, a combination of the unprecedentedchallenges-secularized authoritarian state structures, aWestern-inspired rationalist discourse and Islamicfundamentalist critique since the second half of the 19thcentury-led to a decline in traditional forms of Sufism. Thereconstruction of Sufism teachings which is relevant to thetimes is a necessity. The changing times have an impact on thevalues that led to a moral crisis. Although this century isknown as the victory for the religion, that able to provide ananswer to the crisis of modern man, but it is not in the formof deeds, which tend formalitistic. That need is the spiritual,giving peace and tranquility of spiritual aridity, and also peaceof mind. That can be found in Sufism. However, that hastransformed the paradigm, which is not only a spiritualdimension, however, a social one, or called Social Sufism.